2012
DOI: 10.4103/0975-1483.93578
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Mechanisms Underlying the Gastroprotective Effect of Cymbopogon Citratus Essential Oil

Abstract: Cymbopogon citratus is a medicinal plant popularly used in Brazil for the treatment of various diseases, and the research interest in this plant is justifiable because of its potential medicinal value in stomachache and gastric ulcer. This study was aimed to test the validity of this practice by using experimental models of gastric ulcer and to clarify the mechanisms of gastroprotection by C. citratus leaves essential oil (EOCC). EOCC was evaluated for the ability to protect the gastric mucosa against injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…Increased generation of free radicals by PX-407 induction to rats reduces the activities of antioxidant enzymes such as catalase, GST and SOD as observed in DC group rats. The CCEO treatment presented a significant normalizing effect on these antioxidant enzymes in accordance with earlier findings [32].…”
Section: Discussionsupporting
confidence: 92%
“…Increased generation of free radicals by PX-407 induction to rats reduces the activities of antioxidant enzymes such as catalase, GST and SOD as observed in DC group rats. The CCEO treatment presented a significant normalizing effect on these antioxidant enzymes in accordance with earlier findings [32].…”
Section: Discussionsupporting
confidence: 92%
“…The antioxidant protective mechanism decreases the ROS and scavenges the free radical responsible for the gastric damage and thus inhibit the lipid peroxidation as measured by MDA levels. 3 The findings of this study suggest that chitosan nanoparticle could attenuate oxidative stress by decreasing the lipid peroxidation (MDA level) in the cadmium-treated gastric. A similar result has shown that vitamin C and vitamin E enhanced the antioxidant status and inhibited lipid peroxidation in rats with cadmium chloride toxicity.…”
Section: Discussionmentioning
confidence: 69%
“…2,6 Histopathological examination The tissue of gastric was fixed in a 10% neutral buffered formalin solution, embedded in paraffin and used for histopathological examination with hematoxylin and eosin (H and E) stain. 3…”
Section: Measurement Of Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Têm como sinonímia popular "capim-santo", "capim-limão", "capim-marinho", "capim-cidreira" e "capim-cheiro" 2 . O "capim-santo" tem sido na medicina popular como espasmolítico, analgésico, antiinflamatório, antipirético, diurético, tranquilizante e antimicrobiano 1-3 em doenças ginecológicas e desordens intestinais 4,5 , como diurético, antihemorrágico, carmitativo, excitante digestivo, para males do fígado, no combate a erisipela e tratamento de úlceras crônicas [6][7][8] . O extrato aquoso das folhas de Cymbopogon citratus apresentou atividade hipoglicemiante e hipolipêmica, para as quais se associou a presença de flavonóides e alcalóides 9 .…”
Section: Introductionunclassified